OPEN GOVERNMENT IN GRASSROOT LEVEL GOVERNMENT (STUDY OF WEBSITE QUALITY IN PEJAMBON VILLAGE, BOJONEGORO) - Kusnan Kusnan; Sulikah Asmorowati; Erna Setijaningrum (Jurnal Agregasi : Aksi Reformasi Government dalam Demokrasi, 2021)
This Study have purpose to measure the website quality of Transparency Public Information in Pejambon Village. Website utilization in Government activity progress is the first step e-Government implementation. In Bojonegoro Regency, one of village which successfully implementing the transparency public information based on website is Pejambon Village Government. Village located in the Sumberrejo Sub-District has received many awards, in Regency, Province, and also National. It indicates that Pejambon Village Government has a good quality website, that can be an example for other village. Webqual 4.0 based on community or users perception is the method used to find out the quality of the website. This research is descriptive with quantitative approach. Results of the research showed that website quality of Pejambon Village Government based on usability, information usability, and service interaction quality dimension is in the high category. Keywords: Open Government; Transparency in Public Information; e-Government; Village